2015
DOI: 10.1002/gps.4333
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric hospital admission and long-term care in patients with very-late-onset schizophrenia-like psychosis

Abstract: The patients with VLOSLP needed more psychiatric hospital care than those with earlier illness onset. Ending up in LTC/LLP was equally common in both onset groups, but some physical diseases, such as cardiovascular and respiratory, diminished the likelihood of this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…A study of 918 patients with very late‐onset schizophrenia‐like psychosis, found that these patients needed more psychiatric hospitalisations than patients with earlier onset, but only in the first year after diagnosis, and the difference was rather small (14% and 11%, respectively). Rehospitalisation data are not presented in this study 23 . In our study, the mean age of onset of psychotic disorders was 8 years younger in the rehospitalised group compared to the group that was not rehospitalised, and this was the only variable that approached a statistical trend ( P = .12).…”
Section: Discussioncontrasting
confidence: 51%
“…A study of 918 patients with very late‐onset schizophrenia‐like psychosis, found that these patients needed more psychiatric hospitalisations than patients with earlier onset, but only in the first year after diagnosis, and the difference was rather small (14% and 11%, respectively). Rehospitalisation data are not presented in this study 23 . In our study, the mean age of onset of psychotic disorders was 8 years younger in the rehospitalised group compared to the group that was not rehospitalised, and this was the only variable that approached a statistical trend ( P = .12).…”
Section: Discussioncontrasting
confidence: 51%
“… 2 , 3 , 4 , 5 Older people with very late-onset schizophrenia-like psychosis present with positive psychosis symptoms, typically persecutory delusions with or without multimodal hallucinations, which are distressing, persist for many years, and are associated with increased risks of social dysfunction, institutionalisation, and death. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of outcomes with patients with more typical early adult-onset schizophrenia who have grown old have indicated important differences. Although VLOSLP patients are more likely to be admitted to a psychiatric hospital than comparably aged patients with onset < 60 years, they are not more likely to transition to long-term residential care 58 and have better social functioning as indexed by participation, network size and availability of confidantes. 59 Differences in standardised mortality ratios between VLOSLP (5.02) and early schizophrenia (2.93) are largely explained by increased physical comorbidity and accidents in VLOSLP patients.…”
Section: Treatmentmentioning
confidence: 98%